Wage Formation and Redistribution - Per Engström (Uppsala University, Department of Economics, 2007)
The paper extends the basic Stiglitz (1982) model of optimal nonlinear income taxation into a model featuring endogenous unemployment and wages. This means that the government needs to consider the effects on wages and unemployment when designing the optimal tax function. The tax systems effects on the wage formation and the unemployment rates result in new intricate redistribution channels. A key result of the paper is that the government may, in order to redistribute, use the marginal tax rates to raise the unemployment rate for the high-skilled and lower it for the low-skilled workers.
urn:nbn:se:uu:diva-26530
Keywords: H21; J22; J41; J64; 330; Optimal Non-Linear Income Taxation; Wage Formation; Tax Progressivity; Unemployment; Einkommensteuer; Lohnniveau; Arbeitslosigkeit; Einkommensumverteilung; Qualifikation; Wirtschaftsmodell